Prolonged Hospital Stay in Hypertensive Patients: Retrospective Analysis of Risk Factors and Interactions - Stanisław Surma; Michał Czapla; Izabella Uchmanowicz; Raúl Juárez-Vela; Łukasz Pietrzykowski; Bartosz Uchmanowicz; Marcin Leśkiewicz; Krzysztof Griesmann; Michał Burzyński; Jacek Smereka; Łukasz Lewandowski (Nursing Reports)
Background/Objectives: Arterial hypertension (HT) is a leading modifiable risk factor for cardiovascular diseases, often contributing to prolonged lengths of hospital stay (LOHS), which place significant strain on healthcare systems. This study aimed to analyze the factors associated with prolonged lengths of hospital stay in patients with HT, focusing on key biochemical and clinical predictors. Methods: This retrospective study included 356 adult patients hospitalized in the Cardiology Department of the University Hospital in Wroclaw, Poland, between January 2017 and June 2021. Data collected included demographic characteristics, body mass index (BMI), comorbidities, and laboratory parameters. Logistic regression models were used to identify predictors of prolonged LOHS, defined as four or more days, and to evaluate interactions between variables. Results: Lower levels of low-density lipoprotein cholesterol (LDL-c) and elevated concentrations of high-sensitivity C-reactive protein (hsCRP) were identified as significant predictors of prolonged LOHS, with each 1 mg/dL decrease in LDL-c increasing the odds of prolonged LOHS by 1.21% (p < 0.001) and each 1 mg/L increase in hsCRP raising the odds by 3.80% (p = 0.004). An interaction between sex and heart failure (HF) was also observed. Female patients with HF had 3.995-fold higher odds of prolonged LOHS compared to females without HF (p < 0.001), while no significant difference was found among male patients with or without HF (p = 0.890). Conclusions: The predictors of prolonged LOHS in patients with HT include lower levels of LDL-c, elevated hsCRP, and the interaction between sex and heart failure (HF). Specifically, female patients with HF demonstrated significantly higher odds of prolonged LOHS compared to females without HF, while this relationship was not observed in male patients.